Traffic savings through a cac procedure incorporating a fair bandwidth allocation policy for elastic services - Michael D. Logothetis; Ioannis D. Moscholios; George K. Kokkinakis (Communications - Scientific letters of the University of Zilina, 2004)
We apply the max-min fairness policy (MMF) for elastic services with min and max bandwidth requirements (approximated MMF) not to a single link but to a whole connection-oriented network. To achieve it we propose a Call Admission Control (CAC) procedure consisting of several scenarios dependent on the number of paths between the origin-destination (O-D) network nodes. We evaluate the global network performance at the call level by comparing the maximum Call Blocking Probability (CBP) of the proposed scheme with that of a no fair bandwidth allocation policy scheme. Simulation results show significant traffic savings in the case of the approximated MMF policy.